Investigating the Disseminated Varicella Zoster Virus Infection After Rituximab Use in Nephrotic Syndrome: A Case Report: Disseminated Varicella Zoster - Seyedzadeh, Abolhassan; Tohidi, Mohamadreza; Mohammadi Kamalvand, Mehrnosh (Journal of Pediatric Nephrology, 2023)
The infection with varicella-zoster virus in immune-deficient patients is an important and complex challenge in treating patients and requires decisions on an individual basis. Rituximab is an anti-CD20 positive B cells monoclonal antibody. Nowadays, it is frequently used in patients with idiopathic nephrotic syndrome and makes them susceptible to various infections. In this study, we report a 16-year-old male subject with steroid-resistant nephrotic syndrome who developed a severe and generalized form of chicken pox following rituximab administration.